Ground compensation in pulse induction metal detectors - Ahmet Akgöz; Abdullah Ferikoğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Metal Detectors play an important role especiallyon determining the properties of objects buried in the soil. Groundcompensation is necessary to minimize the faulty warning signals in metaldetectors caused by the mineral structure of the soil. In this study, groundcompensation in pulse induction metal detectors and the effect of metallic soilminerals on metal detectors are examined. A ground compensation softwarealgorithm is developed by implementing a pulse induction metal detector circuitand it is observed in the applied tests that the ground effect is eliminated.